The challenges of consulting the public on science policy: examining the development of European risk assessment policy for genetically modified animals - Hartley, Sarah; Millar, Kate M. (Wiley, 2014)
With the growing importance of public engagement in science policy-making and declining levels of public trust in food production, the European Food Safety Authority (EFSA) has attempted to embed ‘good governance’ approaches to strengthen scientific independence and open-up risk decision-making, which include the use of public consultations. However ‘opening-up’ of risk assessment policies reveals some tensions, namely: balancing the goals of scientific excellence and transparency; protecting science from interests; addressing value judgments; limited opportunities to debate ethical and social issues. EFSA’s development of risk assessment policy for genetically modified animals is used as a case study to analyse these tensions. This analysis suggests that in order to fulfil good governance commitments and maintain trust in risk governance closer cooperation between EFSA and the European Commission is required to provide ‘space’ for debating the broader risk management issues. This publically-accessible space may be needed alongside rather than instead of EFSA’s consultation.